Dry-Cured Meat Products. - Toldrá, Fidel (Publications in food science and nutrition., 2008)
Dry-cured meat products, such as dry-cured ham and dry-fermented sausages, constitute one of the most representative traditional foods that have been produced and consumed throughout history by a diversity of cultures and in different areas of the world. These meat products, which have a high variety of flavors and textures, represent an important part of local economies, particular cultures and gastronomic heritages. Today, there is an important trend to enrich our sensory perceptions, and many consumers and meat industries around the world are getting more and more interested in dry-cured me.